2016
DOI: 10.1039/c6cc00163g
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene-based heparin sensors in competitive aqueous media – the role of self-assembled multivalency (SAMul)

Abstract: Amine-functionalised pyrene derivatives are reported and their ability to detect heparin via a fluorescent response determined - different responses are observed dependent on whether self-assembled multivalent binding between sensor and analyte takes place, and ratiometric heparin sensors which can detect this surgically-relevant polyanion in competitive media are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 46 publications
2
18
1
Order By: Relevance
“…Samples with 10 % plasma suffer from insignificant differences between different heparin concentrations and from the most prominent standard deviations. Similar disruption by increasing plasma concentration in heparin binding has previously been detected in other heparin sensing systems 18 . From the minor standard deviations in 0 and 5 % plasma samples, it can be concluded that large deviations observed in the DLS data do not prevent accurate sensing.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…Samples with 10 % plasma suffer from insignificant differences between different heparin concentrations and from the most prominent standard deviations. Similar disruption by increasing plasma concentration in heparin binding has previously been detected in other heparin sensing systems 18 . From the minor standard deviations in 0 and 5 % plasma samples, it can be concluded that large deviations observed in the DLS data do not prevent accurate sensing.…”
supporting
confidence: 77%
“…From these results, it can be concluded that R16+ and P10+ are the most promising alternatives for heparin binding and sensing. Overall, based on the differences observed here and in the previous studies on the electrostatic binding of heparin 16,18 , multivalency has a high importance in the competitive heparin binding. ITC measurements were conducted to further understand the thermodynamics of the host-heparin binding.…”
contrasting
confidence: 49%
See 2 more Smart Citations
“…We therefore developed a heparin sensor incorporating pyrene. 61 In buffered water, the sensor formed self-assembled multivalent (SAMul) nanostructures providing it with a significant (order of magnitude) improvement in dynamic range. Further, it gave a naked eye response unlike other pyrene derivatives.…”
Section: How Major Surgery Inspired Samul Heparin Binders and Sensorsmentioning
confidence: 99%